Tinjauan Hukum Islam Pada Edaran Pemerintah dan MUI Dalam Menyikapi Wabah Covid-19 Setelah Pemberlakuan New Normal - Cholisa Rosanti (ITB AAS INDONESIA Surakarta, 2021)
This study discusses the Covid-19 virus that is spreading in the world and its handling from the government and MUI after the implementation of new normal according to Islamic law. The government implements a large-scale social restrictions system (PSBB) or social distancing to break the chain of the spread of the covid-19 virus. The government has implemented new normal rules. MUI has issued a notice numbered Kep-1188 / DP-MUI / V / 2020 concerning new normalcy that will be applied by the government such as reopening places of worshipaccording to the health protocol. Nevertheless, this circular is a pros and cons for some people. The purpose of this study is to help the public understand whether the government and MUI circulars in tackling the plague after applying the new normal according to the Shari'a or actually contrary to Islamic Sharia. The research method is the study of literature literature with a normative approach and historical approach. The results of the study showed that the rules imposed by the government and MUI in dealing with the outbreak of Covid-19 pacsa new normal did not disregard Islamic law.